Digital Era and Changes in Consumer Behaviors: An Assessment on Generation C - Akkol Gök, Ayda (Muş Alparslan Üniversitesi, 2020)
In the digital age, the change in technology affects people and life in various ways. Changes have occurred in the purchasing behaviors of the generations living with the conveniences provided by internet technology. It has been an imperative for businesses and marketers to understand and adapt to the changes in consumer behaviors on the one hand and the changes brought by technology on the other. This study surmounted the changes in the consumer behaviors brought by technology. The focus was on the purchasing behaviors of today's consumers, who are almost constantly connected to the internet and each other by mobile devices. The concept of Generation C, which is used to identify these digital consumers has been examined. In the study, the literature was searched to explain the concept and to form a basis for applied research. The concept of Generation C is related the demographic and psychographic features and suggested that these feature groups should be evaluated together in the future studies.

Yaşamakta olduğumuz dijital çağda, teknolojideki değişim insanları ve hayatı çeşitli yönlerden etkilemektedir. İnternet teknolojisinin sağladığı kolaylıklarla yaşamakta olan nesillerin, satın alma davranışlarında değişiklikler ortaya çıkmıştır. İşletmecilerin ve pazarlamacıların bir taraftan tüketici davranışındaki değişiklikleri, diğer taraftan yenilikleri anlaması ve uyum sağlaması bir zorunluluk haline gelmiştir.Bu çalışmada, son yıllarda tüketici davranışlarında teknolojinin etkisiyle ortaya çıkan değişiklikler ele alınmıştır. Mobil cihazlarla neredeyse sürekli olarak internete ve birbirine bağlantılı, sürekli iletişime açık günümüz tüketicilerinin özellikleri ve satın alma davranışları üzerinde durulmuştur. Bu dijital tüketicileri tanımlamada kullanılan C Kuşağı kavramı incelenmiştir. Çalışmada literatür taraması yapılarak kavram açıklanmaya ve uygulamalı araştırmalar için bir temel oluşturulmaya çalışılmıştır. C kuşağı kavramının demografik özelliklerle birlikte psikografik özelliklerle ilgili olduğu ve bu iki özellik grubunun birlikte değerlendirilmesi önerilmektedir.
Dijital Çağ ve Tüketici Davranışlarındaki Değişiklikler: C Kuşağı Üzerine Bir Değerlendirme
anemon
Keywords: Digital marketing; Consumer behaviors; Generation C; Digital Comsumer; Dijital pazarlama; Tüketici davranışları; C Kuşağı; Dijital Tüketici